Mitigating Climate Change through Agroecological Innovations: A Comparative Study on Global Adaptation Strategies - I Made Murdana; Olivier Sossou; Victor Hernandez (Journal of Multidisciplinary Sustainability Asean, 2026)
Background. Climate change poses significant challenges to agricultural systems worldwide, particularly in vulnerable regions. The adoption of agroecological innovations has been recognized as a promising solution to mitigate the effects of climate change and improve the resilience of food systems. These innovations integrate ecological principles into agricultural practices, promoting sustainability, biodiversity, and climate adaptation. However, the effectiveness of these strategies varies across different global contexts, depending on regional environmental, economic, and social conditions. Purpose. This study aims to conduct a comparative analysis of global agroecological adaptation strategies, evaluating their effectiveness in mitigating climate change impacts. It seeks to identify the key factors that contribute to the success or failure of these strategies and to propose recommendations for scaling agroecological practices to address climate challenges. Method. The research employs a comparative case study approach, analyzing agroecological initiatives from diverse regions, including sub-Saharan Africa, Southeast Asia, and Latin America. Data were collected through field visits, interviews with local farmers and experts, and secondary sources such as government reports and academic literature. Results. The findings highlight significant differences in the adoption and outcomes of agroecological practices, with successful strategies often involving community participation, knowledge sharing, and context-specific adaptations. Conclusion. Agroecological innovations offer a viable pathway for climate change mitigation, but their effectiveness depends on local adaptation strategies. Future efforts should focus on strengthening community engagement and policy support for scaling these practices.